PENERAPAN GOOD CORPORATE GOVERNANCE DALAM PENGELOLAAN PERUSAHAAN DAERAH AIR MINUM PT. AIR MANADO - Walangitan, Olivia F. C. (JURNAL ADMINISTRASI BISNIS (JAB), 2017)
PT Air Manado originated from the worsening performance and service of Manado PDAM as a regional company owned by the Manado City government in providing clean water, both in quantity and quality to the community from year to year. Changing the management system of drinking water companies to PT Air requires that all activities and management of this company be adjusted to the system set out in the new PT law which requires the use of Good Corperate Governance standards. The above matters then encourage researchers to conduct further research on Good Corporate Governance at PT Air Manado through research entitled: Implementation of Good Corporate Governance In Management of Regional Water Company PT. Air Manado       This study uses qualitative research methods to illustrate the application of Good Corporate Governance principles based on existing facts as well as company's readiness to manage PT Air Regional Water Company. Then, the existing data collected, classified, interpreted so that will provide information to analyze the problem under study      The results explain that the role of the implementation of good corporate governance in the management of PT. Manado Water is very important to improve the competitiveness of the company in a tight global market competition. Through the implementation of good corporate governance PT. Air Manado will have the ability and power in creating growth and business development according to the target that has been planned. Implementation of good corporate governance that berintikan on corporate culture is an attitude of ethical professionalism and high moral, so that all corporate human power is no longer doing practical politics within the company, but united to improve the company's quality becomes stronger, stronger and healthier and can develop company.Keywords: Good Corporate Governance, PT. Air Manado